Decodable takehome books (Orange) : level B set 1(Books 41-75). (Columbus, Ohio : SRA/McGraw-Hill, 2000)
The SRA Open Court Reading Pre-Decodable Books allow your students to apply their knowledge of phonic element to read simple, engaging texts. Each story supports intruction in a new phonic element and incorporates elements and words that have been learned earlier.
Story Titles: Lance's Dragon--Spice Cake--The Cold Troll--A Chore for Mole--At the Vet--Cupid The Mule--Magic Pages--Steve's Secret--June and the Duke--Dragons Don't Get Colds--The Fancy Party--Sail Day--The Opposum at Night--The King Who was Late--Why, Bly?--The Farmer and the Doe--A Crow, A Goat and a Boat--Tommy's True's Tuba--The Snow Games--Birthday Clues--Who Took My Book?--A Clown Comes to Town--Max the Grouch--Our Town Garden--Sailor Paul and the Crabs--The Knight Who did Not Know--Roy and Big Boy--Little Wren's Surprise--A Photo for Fred--Patty's Awful Day--The Everybody Club--Superhero to the Rescue--Mr. Lee--Princess Julia--How the Rabbit Caught the Tiger.
Keywords: Reading--Study and teaching; Writing--Study and teaching